Genetic thrombophilia and antiphospholipid antibodies in women with early and late preeclampsia: a retrospective cohort study - A. S. Antonova; J. Kh. Khizroeva; V. O. Bitsadze; M. V. Tretyakova; N. A. Makatsariya; E. R. Efendieva; A. Yu. Shatilina; E. M. Lyadnova (Акушерство, гинекология и репродукция, 2025)
Aim: to study a pattern of genetic and acquired thrombophilia in pregnant women with severe early-onset (eoPЕ) and severe lateonset (loPЕ) preeclampsia (PE).Materials and Methods. A retrospective cohort study was conducted from January 2022 to May 2024. A total of 109 pregnant women were examined: group 1 – 45 women with eoPЕ (< 34 weeks of pregnancy), group 2 – 24 women with loPЕ (≥ 34 weeks of pregnancy), group 3 (control) – 40 women with physiologically uncomplicated pregnancy. All pregnant women were examined for lupus anticoagulant (LA) and antiphospholipid antibodies (aPL). The screening test for aPL included the quantitation of IgG/IgM antibodies against cardiolipin, phosphatidylserine, phosphatidylinositol, phosphatidic acid, and β2-glycoprotein 1 in serum or plasma using an enzyme immunoassay. Genetic thrombophilia, homocysteine, and ADAMTS-13 metalloproteinase (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13) levels were also determined.Results. Pregnant women with severe PE more often had genetic forms of thrombophilia (mutations in factor (F) V Leiden gene, prothrombin G20210A, and Thr165Met) and a deficiency of natural anticoagulants (antithrombin and protein S) compared to pregnant women in control group. Women in eoPE vs. loPE group were more often found to carry genetic polymorphisms in the plasminogen activator inhibitor-1 (PAI-1) and fibrinogen genes. Also, in the group of pregnant women with eoPE, the circulation of aPL, ADAMTS-13 inhibitor, and elevated homocysteine levels were more common. Pregnant women with loPE were older and more often suffered from hypertension, diabetes mellitus, and excess body weight. No significant differences between eoPЕ and loPЕ groups were found while comparing prevalence of autoimmune diseases, thrombosis in familial history, mutations in FV Leiden gene (heterozygous form), FII prothrombin gene G20210A (homozygous form), FII prothrombin gene Thr165Met (heterozygous form), antithrombin III deficiency, protein S deficiency.Conclusion. Precise causes underlying PE remain unknown, andwe are still far from understanding all the molecular, immunological, genetic, and environmental mechanisms that lead to the various clinical manifestations of placental syndromes including PE. However, the study results suggest that the presence of thrombophilic disorders, especially in the fibrinolytic system, and aPL circulation contribute to eoPE pathophysiology or progression.